Persahabatan Dalam Perspektif Neo-Thomisme Yoseph Pieper - Sermada Kelen Donatus (Sekolah Tinggi Widya Sasana, 2020)
Neo-thomism is a school of philosophy that revives the philospical-theological thoughts of Thomas Aquinas. This article contains of the thoughts of Yoseph Pieper, a German Catholic philosopher who follows Neo-Thomism. Joseph Pieper’s works show their root to Thomas Aquinas’ philosophy. Pieper’s concepts on man and society, as discussed in this article, become the writer’s perspective to convey the concept of friendship which concluded from Pieper’s concept about an ideal Christian: a man of faith, hope, love, temperance, justice, courage, and prudence.